Control : exposing the truth about guns - Beck, Glenn, frey50; Balfe, Kevin; Beck, Hannah (New York Threshold Editions/ Mercury Radio Arts, 2013)
"Bestselling author and popular radio and television host Glenn Beck shines a spotlight on today's culture of violence and provides practical, timely, and fact-based answers to the most commonly heard gun-control arguments."--Publisher's description.
Pt. 1. The truth about guns -- pt. 2. Winning hearts and minds.
Keywords: Gun control -- United States; Violence -- United States; Firearms -- Law and legislation -- United States; Firearms ownership -- United States; Firearms -- Law and legislation; Firearms ownership; Gun control; Violence; United States